Role of RGS17 in cisplatin-induced cochlear inflammation and ototoxicity via caspase-3 activation - Al Aameri, Raheem F. H.; Alanisi, Entkhab M. A.; Al Sallami, Dheyaa; Alberts, Ian; Tischkau, Shelley; Rybak, Leonard P.; Ramkumar, Vickram (Frontiers in Immunology, 2025)
Cisplatin is a chemotherapy drug used to treat different solid tumors, including ovarian, bladder, lung, and head and neck cancers. One of its significant side effects is ototoxicity, especially when high doses are required. Cisplatin-induced ototoxicity is associated with increased cochlear cell death resulting from DNA damage, caspase activation, oxidative stress, inflammation, and glutamate excitotoxicity. The regulator of G protein signaling 17 (RGS17), a member of the RGS-RZ subfamily, hastens the hydrolysis of GTP to GDP on the Gα subunit. In the current study, we demonstrate the role of RGS17 in cisplatin-induced cochlear inflammation and ototoxicity. C57BL/6J mice treated with two cycles of cisplatin (3.5 mg/kg) showed a significant elevation in ABR thresholds, along with loss of outer hair cells and inner hair cells synapse. Furthermore, immunohistochemical analysis revealed that cisplatin administration upregulates CXCL1, accompanied by an increase in the number of CD45 and CD68-positive immune cells. On the other hand, RGS17 knockout in hair cells protects against cisplatin-induced elevation of ABR thresholds, outer hair cell loss, cochlear inflammation, and inner hair cell synaptopathy. Moreover, RGS17 knockout downregulates CXCL1 immunolabeling and decreases the number of CD45 and CD68-positive immune cells induced by cisplatin. These results suggest that RGS17 is implicated in cisplatin ototoxicity, potentially by initiating the immune cascade, and indicate RGS17 as a relevant target for treating cisplatin ototoxicity.